Tinjauan etika hukum Islam terhadap pemerkosaan dalam perkawinan: Analisis prinsip mu'asyarah bi al-ma‘ruf dan darar ma‘nawi - Mulia, Siti Musdah; Launa, Belqiatuz Zahro; Ibrahim, Norliah (Prodi Hukum Keluarga Islam Fakultas Syari'ah Universitas Islam Zainul Hasan Genggong Probolinggo, 2025)
This research examines the position of marital rape in the perspective of Islamic legal ethics. In the current context, this issue has become a critical spotlight, especially in the discourse of gender justice and rights in marriage. The purpose of this research is to construct the view of Islamic law related to the act of forced sexual intercourse in marriage by tracing normative sources in fiqh, such as the Qur'an, hadith, and the opinions of scholars through the ijtihad approach. The method used in this research is a normative qualitative approach by analyzing classical and contemporary Islamic texts. The results of the study show that marital rape contradicts the principle of mu'asyarah bi al-ma'ruf (good treatment in the relationship between husband and wife) and causes darār ma'nawi or psychological harm to the wife as a victim. This act also violates the principle of equality in the fulfillment of biological rights between spouses, as taught in Islamic legal values that uphold justice and compassion.